Challenges in the Detection of Clinically Useful Biomarkers for the Diagnosis of Delirium in Older People in the Emergency Department—A Case–Control Study - Angela Soler-Sanchis; Francisco Miguel Martínez-Arnau; José Sánchez-Frutos; Pilar Pérez-Ros (Life, 2022)
Background: The identification of biomarkers associated with delirium in the emergency department could contribute to the understanding, prediction and diagnosis of this disorder. The present study was carried out to identify biomarkers included in easily and quickly obtained standard blood examinations in older patients with delirium in the emergency department. Methods: A case–control study was carried out in the emergency department of Francesc de Borja Hospital (Gandía, Valencia, Spain). Older adults (≥65 years of age) diagnosed with delirium (n = 128) were included. Cases due to alcohol or substance abuse were excluded. Controls were selected on a randomized basis from the remaining patients (n = 128). All laboratory test parameters included in the routine blood and urine tests of the emergency department were collected. Results: The mean age of the patients was 81.24 ± 7.51 years, and 56.2% were males, while the mean age of the controls was 78.97 ± 7.99 years, and 45.3% were males. Significant differences were found between the cases and controls in relation to the following parameters: urea 43 (32–58) mg/dL versus 50 (37–66) mg/dL, respectively; neutrophils 69.6 (62.05–78.75)% versus 75.5 (65.1–83.2)%; monocytes 8.7 (7–10.4)% versus 7.6 (5.5–9.2)%; platelets 213 (159–266) × 109/L versus 224 (182–289) × 109/L; neutrophil–lymphocyte ratio 3.88 (2.45–7.07) versus 5 (2.75–8.83); platelet–lymphocyte ratio 281.4 (210–360) versus 357.1 (257.8–457.1); and mean platelet volume 10.6 (10–11.5) fl versus 10.4 (9.67–10.9) fl. Although the mean values were above desirable levels in both groups, they were higher for most parameters in the control group. No significant differences were observed in C-reactive protein concentration (9.99 (1.69–51) mg/L versus 12.3 (3.09–65.97) mg/L). Conclusions: The identification of delirium biomarkers poses difficulties due to the urgent nature of the disorders found in older people admitted to the emergency department. Research in this field is needed, since it would allow early identification and treatment of delirium.